Stabilization of eye drops containing autologous serum and recombinant human epidermal growth factor for dry eye syndrome - Sriwidodo Sriwidodo; Insan Sunan Kurniawan Syah; Iman Permana Maksum; Toto Subroto; Ulvi Zasvia; Abd Kakhar Umar (Journal of Advanced Pharmaceutical Technology & Research, 2020)
Human epidermal growth factor (hEGF) and autologous serum are considered safer and more effective in treating dry eye syndrome. However, suitable formulas and preparation methods are needed to obtain eye drop containing autologous serum and hEGF, which are stable during storage and use. Therefore, this study aimed to develop a stable and effective eye drops containing autologous serum and hEGF. Stabilization of autologous serum and hEGF was done by adding lyoprotectant and antioxidant agents, and then prepared using the freeze-drying method. The clarity, pH, sterility, and endotoxin content of the preparation were evaluated. The effectiveness of the preparation was assessed by a cell viability test using a WST-8 reagent. Based on the results, all formulas produce preparations that are isotonic, clear, sterile, stable, and free from endotoxins. Cell viability test shows the addition of 25 μg/mL hEGF increased epithelial cell proliferation by up to 197%. It can be concluded that eye drops containing autologous serum and 25 μg/mL hEGF can be a promising therapy for dry eye syndrome.